Human Capital Auditierung - Aufgabe für das Personalmanagement Grundlagen, Verfahren, Anwendungen - Armutat, Sascha; Friederichs, Peter (wbv Publikation, 2012)
For the Human Resource Management in a company the systematic management of Human Resources plays an important role. The editors inform about important topics and trends within the Human Capital Management and provide an insight into the tasks of a Human Capital Auditor. The authors present methods and processes to evaluate Human Capital and discuss the importance of ethically orientated leadership. The publication sensitises for the opportunities and approaches of Human Capital Management within a company. Für das Personalmanagement im Unternehmen spielt das systematische Management der Humanressourcen eine wichtige Rolle. Die Herausgeber informieren über wichtige Themen und Trends im Human Capital Management und geben einen Einblick in die Aufgaben eines Human Capital Auditors. Die Autoren stellen Methoden und Verfahren zur Bewertung von Human Capital vor und diskutieren die Bedeutung von ethikorientierter Führung. Der Band sensibilisiert für die Möglichkeiten und Ansatzpunkte des Human Capital Managements im Unternehmen
Keywords: Bewertung von Human Capital; Führung; Human Capital; Human Capital Auditierung; Human Capital Auditor; Human Capital Management; Human Resources; Humankapital; Humanressourcen; Leadership; Management; Personal; Personalentwicklung; Personalmanagement